Solvent-regulated preparation of well-intercalated Ti3C2Tx MXene nanosheets and application for highly effective electromagnetic wave absorption. (20th June 2018) - Xu, Gengfang; Wang, Xiaoxia; Gong, Shida; Wei, Shuang; Liu, Jingquan; Xu, Yuanhong
Abstract: MXene-derived nanostructures provide the possibility of meeting the requirements of strong absorption, thin thickness and flexible layer for electromagnetic (EM) wave absorption. However, exploration of pure and well-intercalated MXene nanosheets for efficient EM wave absorption is still in the nascent stages. Herein, Ti3 C2 Tx nanosheets with solvent-manipulated properties were achieved via ultrasonication-solvothermal treatment of bulk Ti3 C2 Tx in different solvents including dimethylformamide (DMF), ethanol, and dimethyl sulfoxide (DMSO), respectively, because of their combined influences of molecular size, oxidation capability, and boiling point. Especially, it was found that a larger layer space and less oxidation effects on the Ti3 C2 Tx nanosheets were observed upon solvothermal treatment in DMF than those in ethanol or DMSO treatment. As a result, the DMF-treated Ti3 C2 Tx nanosheets can be used as highly effective dielectric materials for EM wave absorption. The reflection loss value reached −41.9 dB (more than 99.99%) at 13.4 GHz with the sample thickness of only 1.1 mm. Characterization techniques including scanning electron microscopy, transmission electron microscopy, atomic force microscopy, x-ray diffraction, x-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and density functional theory calculation were used to elaborate the possible mechanisms.